Cendakimab in Patients With Moderate to Severe Atopic Dermatitis: A Randomized Clinical Trial - Blauvelt, Andrew; Guttman-Yassky, Emma; Lynde, Charles; Khattri, Saakshi; Schlessinger, Joel; Imafuku, Shinichi; Tada, Yayoi; Morita, Akimichi; Wiseman, Marni; Kwiek, Bartlomiej; Machkova, Martina; Zhang, Peijin; et al. (JAMA dermatology, 2024)
IMPORTANCE: Cendakimab selectively targets interleukin (IL)-13, a type 2 cytokine implicated in atopic dermatitis (AD) pathogenesis, by inhibiting binding to its receptors (IL13R-α1 and IL13R-α2). Proof-of-concept work in AD supports using cendakimab for type 2 inflammatory diseases. OBJECTIVE: To evaluate the efficacy and safety of cendakimab compared with placebo in patients with moderate to severe AD. DESIGN, SETTING, AND PARTICIPANTS: This phase 2, randomized, double-blind, placebo-controlled, parallel-group, dose-ranging clinical trial was conducted from May 2021 to November 2022. Adult patients with moderate to severe AD and inadequate response to topical medications were enrolled at 69 sites in 5 countries (US [n = 26], Japan [n = 17], Canada [n = 9], Poland [n = 9], and Czech Republic [n = 8]). Data were analyzed between April 25, 2023, and October 16, 2023. INTERVENTIONS: Patients were randomized (1:1:1:1) to receive subcutaneous cendakimab, 360 mg, every 2 weeks; 720 mg, every 2 weeks; 720 mg, once weekly; or placebo. MAIN OUTCOME AND MEASURE: Mean percentage change in Eczema Area and Severity Index scores from baseline to week 16. Hierarchical testing with multiplicity adjustment was performed for 720 mg, once weekly vs placebo, then 720 mg, every 2 weeks vs placebo, and then 360 mg, every 2 weeks vs placebo. RESULTS: Overall, 221 patients were randomized, and 220 received study drug (95 women [43%]; mean [SD] age, 37.7 [13.9] years; 720 mg, once weekly [54 (24%)]; 720 mg, every 2 weeks [55 (25%)]; 360 mg, every 2 weeks [55 (25%)]; placebo [56 (26%)]). The primary efficacy end point was met for cendakimab, 720 mg, once weekly vs placebo (-84.4 vs -62.7; P = .003) but missed statistical significance for 720 mg, every 2 weeks (-76.0 vs -62.7; P = .06). The treatment effect for 360 mg, every 2 weeks (-16.3; nominal P = .03 vs placebo) was comparable with 720 mg, once weekly (-21.8); however, significance was not claimed because the hierarchical testing sequence was interrupted. Of patients with treatment-emergent adverse events leading to discontinuation, 4 (7.4%) received 720 mg, once weekly; 2 (3.6%) 720 mg, every 2 weeks; 1 (1.8%) 360 mg, every 2 weeks; and 2 (3.6%) placebo. CONCLUSIONS AND RELEVANCE: The results of this randomized clinical trial indicated that cendakimab was effective, generally safe, and well-tolerated in patients with moderate to severe AD. The primary end point was met with a significant reduction in Eczema Area and Severity Index scores with 720 mg, once weekly at week 16. Cendakimab demonstrated progressive AD improvement at all doses during 16 weeks of treatment. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT04800315.
Keywords: Dermatitis, Atopic; lidé; Middle Aged; výsledek terapie; injekce subkutánní; Adult; stupeň závažnosti nemoci; Female; Antibodies, Monoclonal, Humanized; vztah mezi dávkou a účinkem léčiva; Humans; Dose-Response Relationship, Drug; atopická dermatitida; Double-Blind Method; Interleukin-13; interleukin-13; lidé středního věku; mužské pohlaví; mladý dospělý; Injections, Subcutaneous; ženské pohlaví; Young Adult; Severity of Illness Index; Treatment Outcome; Male; humanizované monoklonální protilátky; dvojitá slepá metoda; dospělí